Identification of taxonomic and thematic relationships: Do the two semantic systems have the same status in semantic dementia?. Issue 9 (21st October 2019) - Merck, Catherine; Noël, Audrey; Jamet, Eric; Robert, Maxime; Hou, Camille; Salmon, Anne; Belliard, Serge; Kalénine, Solène
ABSTRACT: Introduction : Disequilibrium between the taxonomic and thematic semantic systems was previously hypothesized in participants with semantic dementia (SD), without rigorously assessing their ability to identify the two types of semantic relationships. Therefore, the aim of the present study was to directly compare the ability of 10 participants with SD, 10 participants with Alzheimer's disease (AD), and 20 controls to identify thematic versus taxonomic relationships. Methods : Participants performed an explicit forced-choice picture-matching task in which they had to determine which of two pictures of choice was semantically related to the target picture. Target pictures could display natural or artifact objects. Each target was presented once with a taxonomically related picture and once with a thematically related picture. Results : Analyses of correct thematic and taxonomic matches as a function of target domain showed that the performance of the two groups of patients differed in the taxonomic conditions but not in the thematic conditions, demonstrating a relative preservation of thematic knowledge in SD. Additional correlation analyses further indicated that the particular status of thematic relationships in SD was even stronger for artifact concepts. Conclusions : Results provide evidence of the heterogeneous nature of semantic knowledge disruption in SD, and could be regarded as being consistent with the existence of two neuroanatomically and functionally distinct semantic systems. Results further stress the relevance of performing a more detailed and complete assessment of semantic performance in participants with SD, in order to capture the impaired but also preserved aspects of their knowledge.